RANCANG BANGUN BUKA TUTUP TEMPAT SAMPAH OTOMATIS MENGGUNAKAN ARDUINO UNO (INFRARED BARRIER SENSOR) DAN ULTRASONIK UNTUK MENDETEKSI SAMPAH YANG SUDAH PENUH - Wicaksono, Guntur Adi; Hidayat, Imam; Wijaya, Sugeng Hendra; Akbar, Raden Ilham (Universitas Bakti Indonesia, 2024)
Nowadays, human life often cannot be separated from technological developments which are becoming more and more advanced day by day. This can be seen from various equipment that has an automatic work system, so that human intervention in controlling is very small, humans try to overcome problems that arise around them and make existing work easier. designing a system to open and close the trash can automatically using Arduino Uno. This research uses the Research and Development (R&D) method to develop a design for an automatic trash can and detect trash that is full. The aim is to increase the usability of products that were originally manual to automatic products, enabling them to make it easier to dispose of waste. With this product, dispose of trash automatically and avoid germs in the trash, saving time and effort. Thus, this research makes a valuable contribution to improving the quality of life in an automated society and solving challenges in technological progress